White-nose syndrome is associated with increased replication of a naturally persisting coronaviruses in bats. Issue 1 (December 2018) - Davy, Christina; Donaldson, Michael; Subudhi, Sonu; Rapin, Noreen; Warnecke, Lisa; Turner, James; Bollinger, Trent; Kyle, Christopher; Dorville, Nicole; Kunkel, Emma; Norquay, Kaleigh; Dzal, Yvonne; et al.
Abstract Spillover of viruses from bats to other animals may be associated with increased contact between them, as well as increased shedding of viruses by bats. Here, we tested the prediction that little brown bats (Myotis lucifugus ) co-infected with theM. lucifugus coronavirus (Myl -CoV) and withPseudogymnoascus destructans (Pd ), the fungus that causes bat white-nose syndrome (WNS), exhibit different disease severity, viral shedding and molecular responses than bats infected with onlyMyl -CoV or onlyP. destructans . We took advantage of the natural persistence ofMyl -CoV in bats that were experimentally inoculated withP. destructans in a previous study. Here, we show that the intestines of virus-infected bats that were also infected with fungus contained on average 60-fold more viral RNA than bats with virus alone. Increased viral RNA in the intestines correlated with the severity of fungus-related pathology. Additionally, the intestines of bats infected with fungus exhibited different expression of mitogen-activated protein kinase pathway and cytokine related transcripts, irrespective of viral presence. Levels of coronavirus antibodies were also higher in fungal-infected bats. Our results suggest that the systemic effects of WNS may down-regulate anti-viral responses in bats persistently infected withM. lucifugus coronavirus and increase the potential of virus shedding.